The The Cultural Value of Everyday Identity in Ghanaian Popular Video Movies - Ramatu Mustapha Dadzie (Modern Africa)
Discourses on Ghanaian video movies have predominantly been described as representing everyday life. Conversely, the approach to which the everydayness of the video movies has been viewed diminishes the cultural value of the narratives. This article examines how movie narratives capture daily life experiences and how they respond to the anxieties that characterise everyday life. Using qualitative research methods, a contextual analysis of six movies was employed in analysing the narratives. Representations of daily life are embodied in marriage, religion, family, social relations and economic conditions. Anxiety is expressed over family disintegration, consumer culture intersecting with religious beliefs and the interplay between individual aspirations and social expectations in contemporary living. This study broadens the conversation on the relevance and contribution of video films to both cinema and cultural studies.